Diarrhea, Dysbiosis, Dysfunction, and the Disastrous Global Health Consequences: Piecing the Puzzle Together. (1st January 2022) - Frese, Steven; Riddle, Mark S.
Abstract : Abstract: The burden of diarrheal infections globally, including the chronic health consequences, is an important problem. Herein we describe a recent paper published by the Journal and describe how it fits within and advances our knowledge in this area.